Sustainable Tourism Development: A Study of the Development of Pasar Sawahan Tourism in Kalongan Village - Sulaeman Fityan Saputra; Fadhila Kayla Zefara; Bagas Firzi Firmansyah; Diana Fitriyani; Ammela Maulani; Arneta Dyah Selina; Hanum Arumningtyas; Yudi Siswanto (LP2M INSURI Ponorogo, 2026)
The development of tourism villages has become a key strategy in Indonesia’s rural development to support economic growth, cultural preservation, and environmental sustainability in line with the Sustainable Development Goals (SDGs). However, many tourism villages still face challenges in applying sustainable tourism principles, especially those with limited institutional capacity and governance. Pasar Sawahan tourism in Kalongan Village is a community-based destination with strong local wisdom but still faces challenges in infrastructure, environmental management, and governance. Previous studies tend to focus on tourism villages in general, while limited research examines sustainability in traditional community-based tourism markets. This study aims to analyze the implementation of sustainable tourism principles and identify key challenges in Pasar Sawahan. Using a qualitative phenomenological approach, data were collected from eight participants through interviews, observation, and documentation, and analyzed using the Miles and Huberman model. The results show sustainability efforts through community participation, MSME empowerment, cultural preservation, and environmental programs, although challenges remain in institutional strengthening, digital promotion, and youth involvement.